ANALISIS PENGUASAAN KATA BENDA KETERANGAN POSISI â€œYILAIâ€ DAN â€œYIHOUâ€ PADAMAHASISWAPENDIDIKAN BAHASAMANDARIN - Mirnawati, Nona; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractNoun is word that represent people, things, times, and places. According to the meaning, noun is divided into six categories, one of them is the prepositionã€‚ The example of the preposition were â€œyilaiâ€ and â€œyihouâ€. In the Chinese learning class, some learners were misunderstood with the use of the two words and misused them. There were also some errorsÂ in the application of the words. The author examined students of Chinese Teacher Education of Tanjungpura university in academic year 2016. The author examined the learners â€˜mastery of the preposition â€œyilaiâ€ and â€œyihouâ€ and analyzed the learnersâ€™ difficulty in learning the preposition â€œyilaiâ€ and â€œyihouâ€. The result of the research showed that the students of Chinese Teacher Education of Tanjungpura university in academic year 2016 were more able touseandunderstand â€˜yihouâ€™ rather than the use of â€˜yilaiâ€™. The percentage of â€œyihouâ€ was 66%, while â€œyilaiâ€ was only 61%.Â Â Keyword: preposition, yilai, yihou, the analysis of mastery